2007
DOI: 10.3343/kjlm.2007.27.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hemostatic Changes in Patients with Sepsis

Abstract: Background : It is known that severe infection and inflammation lead to hemostatic abnormalities. Recently, much attention is focused on the mechanisms of infection or inflammation and on how it plays a central role in effecting the coagulation system. Disseminated intravascular coagulation in particular, is a common phenomenon in patients with sepsis, but the clinical implications of this condition are not clear. Therefore we attempted to evaluate the changes of the coagulation system in patients with sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…As a result, the prolongation of aPTT may be masked by an increase in factor VIII levels in early sepsis patients with DIC. Kinasewitz et al ( 20 ) and Kim et al ( 19 ) reported that the abnormality rate in PT is hihger than that in aPTT (93.4% vs. 63.1% and 68.4% vs. 47.3%, respectively) for patients with sepsis. In conclusion, we suggest that PT is an early marker for the detection of DIC, and aPTT is a marker for the reflection of severity in DIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the prolongation of aPTT may be masked by an increase in factor VIII levels in early sepsis patients with DIC. Kinasewitz et al ( 20 ) and Kim et al ( 19 ) reported that the abnormality rate in PT is hihger than that in aPTT (93.4% vs. 63.1% and 68.4% vs. 47.3%, respectively) for patients with sepsis. In conclusion, we suggest that PT is an early marker for the detection of DIC, and aPTT is a marker for the reflection of severity in DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Gando et al ( 7 ) made the R-JAAM criteria based on the little effect of fibrinogen level on the prediction of outcome in the DIC patients. However, Kim et al ( 19 ) showed that the OR of the low fibrinogen level (< 1.0 g/L) is 2.13 ( P = 0.024) and Gando et al ( 16 ) reported that the fibrinogen is an independent predictor for 28-day mortality (OR 0.998, P = 0.033). The present study showed that fibrinogen on Day 1 transformed to nominal variable is an independent predictor for ICU mortality in univariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen increase, an acute-phase protein, is also observed in diabetic patients without vascular diseases [10e13] as well as in patients with sepsis [14]. A high fibrinogen concentration is among the factors promoting nutritive capillary blood flow disruption leading to tissue ischemia [15] and some evidence suggests a diabetic foot amputation risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the coagulation cascade has also been described in so-called inflammation-induced coagulation (14), in which some proinflammatory cytokines, such as interleukin-1 (IL-1), interleukin-6 (IL-6), and the tumor-necrosis factor (TNF), determine an increased inducible tissue factor expression in some cell types, such as endothelial cells and monocyte-derived macrophages (4,5).…”
mentioning
confidence: 98%
“…Basic inclusion criteria were: [1] diagnosis of PID on patient's admission to hospital (based on clinical evaluation, laboratory reports, ultrasonographic examination, and, for surgical patients, on laparoscopy/laparotomy evidence), confirmed on discharge; [2] lack of subjective and/or objective findings, either suggestive or indicative of ongoing thromboembolic processes or of other diseases related to elevated D-dimer values; [3] lack of subjective and/or objective findings, either suggestive or indicative of other diseases (e.g., endometriosis, ectopic pregnancy) with similar clinical features; [4] declared desire to maintain reproductive organs; and [5] no reported history of sexually transmitted diseases.…”
mentioning
confidence: 99%